1970
DOI: 10.3329/jbs.v17i0.7095
|View full text |Cite
|
Sign up to set email alerts
|

Cytological Effect of Herbicides on Hexaploid Wheat (<i>Triticum aestivum</i> L.)

Abstract: Context: In order to control weeds many chemicals are being used. It is well known that the chromosomal constitution of the cells may be changed as a result of herbicide treatment.Objectives: This investigation was made to study the cytological effects of herbicides on somatic and germ cells of hexaploid wheat. Materials and Methods:Two herbicides namely, Fielder and Ronstar were used with three different concentrations along with control. Treatment duration was 12 hours for each of the concentrations. Seeds o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…The present study showed that with the increase of herbicides concentration there was an increase in interphase chromosome volume in case of both the Topstar and Fielder than the control. This result showed resemblance with Akhter et al (2009) who stated that interphase chromosome volume of hexaploid wheat was found to be increased in case of Ronstar with increasing the concentration of herbicides. It was found in the present investigation that mitotic index was decreased with the increased doses of herbicide Fielder and found to be the highest in control.…”
Section: Discussionsupporting
confidence: 73%
“…The present study showed that with the increase of herbicides concentration there was an increase in interphase chromosome volume in case of both the Topstar and Fielder than the control. This result showed resemblance with Akhter et al (2009) who stated that interphase chromosome volume of hexaploid wheat was found to be increased in case of Ronstar with increasing the concentration of herbicides. It was found in the present investigation that mitotic index was decreased with the increased doses of herbicide Fielder and found to be the highest in control.…”
Section: Discussionsupporting
confidence: 73%
“…The decrease in mitotic index is slightly dose dependent, it does not affect the percentage of mitotic stages [15]. On the contrary the mitotic index were high as well as low in most of the treatments compared to that of control but did not show any clear relationship based on increasing or decreasing doses of herbicides as reported by [16]. In the present study the mitotic divisions were found to be inhibited at higher concentration.…”
Section: Resultssupporting
confidence: 54%
“…This brings to the sub chromatid association; apart from the above stickness might be the result of action of herbicides on the protein of the chromosome [23]. Chromosomal bridges have been reported following treatment with number of chemicals including 2,4-D and isoproturon on wheat [21], Fieldr and Ronstar on wheat [16], imazethapyr on wheat [19], ethylene glycol on wheat [28], putrescine on wheat [24], maleic hydrazide on Trigonella [25], illoxan on Allium cepa [15]. Presence of chromosomal bridge may be due to stickness or formation of dicentric chromosome caused by breakage and reunion [25].…”
Section: Resultsmentioning
confidence: 99%
“…However, herbicides did not affect the MI, which changed only slightly for the highest concentration (2.0 mg/mL). The absence of a decrease in the MI was described by Akhter et al [47], when studying the cytological effects of herbicides on hexaploid wheat Triticum aestivum L. At the same time, a number of studies showed, that individual pesticides in high concentrations negatively affect MI. So, in the Allium cepa test herbicides quizalofop-p-ethylandcycloxydimin concentrations 0.5, 1.0% and 1.5%, showed a strong cytotoxic effects.…”
Section: Discussionmentioning
confidence: 83%